2016
DOI: 10.1148/radiol.2015150364
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond the Cuff: MR Imaging of Labroligamentous Injuries in the Athletic Shoulder

Abstract: Shoulder disease is common in the athletic population and may arise as a consequence of a single traumatic episode or multiple repeated events. Associated labroligamentous injuries can result in substantial disability. Specific athletic and occupational activities result in predictable injury patterns. Imaging in general and magnetic resonance (MR) imaging, in particular, are vital in establishing the correct diagnosis and excluding common mimicking conditions, to ensure timely and appropriate management. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 110 publications
0
8
0
2
Order By: Relevance
“…Many anatomic and radiographic measurements of the coracoid process have been reported [17,18,29,30]. Kawasaki et al reported the cross-sectional size at the level of the coracoid base by a study on CT axial measurement of the coracoid base [7].…”
Section: Discussionmentioning
confidence: 99%
“…Many anatomic and radiographic measurements of the coracoid process have been reported [17,18,29,30]. Kawasaki et al reported the cross-sectional size at the level of the coracoid base by a study on CT axial measurement of the coracoid base [7].…”
Section: Discussionmentioning
confidence: 99%
“…Many anatomic and radiographic measurements of the coracoid process have been reported [14,15,20,23]. Yoshiteru Kawasaki et al reported the cross-sectional size at the level of the coracoid base by the study on CT axial measurement of the coracoid base [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pathologies of the posterior labrocapsular and ligamentous complex include reverse Bankart, reverse humeral avulsion of the glenohumeral ligament, extended superior labral anteroposterior tear, posterior labrocapsular periosteal sleeve avulsion, reverse glenolabral articular disruption, and Kim lesions. 7,[10][11][12] Literature indicates that only 2% of patients with shoulder instability present with posterior subluxation. 11 A reverse Bankart lesion is known as separation of the posteroinferior labrum secondary to macrotrauma; however, numerous variants of posterior glenoid labral lesions have also been described in the literature.…”
Section: Discussionmentioning
confidence: 99%